De-constitutionalization and majority rule: A democratic vision for Europe - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2016)
European integration has come to constrain the capacity for democratic political action in EU member states through the judicial constitutionalization of "economic liberties," whereas the capacity for effective political action at the European level is narrowly constrained by the multiple-veto character of the Union's "ordinary legislative procedure." Since both of these constraints have institutional causes, they might be loosened by institutional reforms that shift the competence for negative integration from the sphere of judicial legislation to European political legislation and would allow legislation by majority rule at the European level. In order to ensure democratic legitimacy, however, majoritarian legislation would have to allow national opt-outs. – – Die europäische Integration hat den Handlungsspielraum demokratischer Politik in den Mitgliedstaaten durch die richterrechtliche Konstitutionalisierung der ökonomischen Grundfreiheiten beschränkt. Gleichzeitig wird aber effektives politisches Handeln auf der europäischen Ebene durch den hohen Konsensbedarf des "ordentlichen Gesetzgebungsverfahrens" behindert und oft verhindert. Beide Beschränkungen könnten durch institutionelle Reformen gelockert werden, die einerseits die Kompetenz zur Definition der negativen Integration von der richterlichen auf die politische Gesetzgebung übertragen, und die andererseits europäische Gesetzgebung mit einfacher Mehrheit ermöglichen. Das majoritäre Verfahren wäre freilich nur in Verbindung mit der Möglichkeit nationaler Opt-outs demokratisch legitimiert.
Keywords: 300; EU; democracy; legitimacy; consensus; majority; negative integration; liberalization; constitutionalization; Demokratie; Legitimität; Konsens; Mehrheit; negative Integration; Liberalisierung; Konstitutionalismus